Bottom-up characterisation of the Italian residential building stock - Archetype buildings and energy demand - Frateily, Umberto (My University, 2014)
This work describes the Italian residential building stock by means of archetype buildings representative of the stock. The aggregated description is conducted following a methodology proposed previously that consists of three steps: the segmentation, which defines the archetype buildings; the characterization, which delineates the physical properties of the buildings and the quantification; which establishes the number of archetype buildings of each type representative for a certain group of buildings. Afterwards, the archetypes description is used as input to the building-‐stock model “Energy, Carbon and Cost Assessment of Building Stocks” (ECCABS) to simulate the final energy demand of the building stock. The model results, related to a chosen reference year, are compared with corresponding data given by the statistical databases to validate the building-‐stock description. The Italian residential building stock is represented by 70 archetype buildings, corresponding to 2 building typologies, 7 periods of construction and 5 climate zones. The calculated final energy demand is 417,7 TWh/year for the residential sector, thus showing a deviation which fluctuate between 15% and 28% with respect to the energy demand given by the statistics. A final discussion of the results and an assessment of suitability of the model have been carried out. In addition a sensitivity analysis has been accomplished to evaluate the most influential variables of the model, which are: HW, SW, Trmin, U-‐values. This work contributes to a European building stock database, and will be used as a basis to assess the effects of measures related to the energy efficiency and energy savings.
Keywords: Energiteknik; Energy Engineering